大规模可再生能源接入下的电力系统充裕性优化 ：(二)多等级备用的协调优化 = Adequacy optimization for a large-scale renewable energy integrated power system part two collaborative optimization of multi-grade reserve - 宋晓芳 Song, Xiaofang (2019)
随着间歇性可再生能源接入比例的逐步提高，系统所需备用容量也相应增加。如果仅采用旋转级备用提供系统备用容量，不仅从经济上不可行，长期维持高比例的旋转级备用容量引起的排放也违背了可再生能源发展的初衷。调节性能灵活的非旋转级备用提供备用服务，有助于提升系统充裕性，是促进高比例可再生能源消纳的重要途径。针对现有非旋转级备用优化研究的不足，首先，文中分析了市场机制下发电侧和需求侧非旋转级备用的调度模式及优化模型。然后，考虑到旋转级备用与非旋转级备用在不同充裕性事件场景下存在物理-经济特性方面的差异性及互补性，进一步提出了综合考虑旋转、非旋转备用的混合优化方法。最后，通过算例分析，验证了所提优化方法的可行性和有效性。With the gradual increase of the intermittent renewable energy generation, the demand of system reserve capacity is raised accordingly. The pure use of spinning-grade reserve for supporting reserve capacity to the system will not only cause economic problems, but also lead to high CO2 emission from long-term maintenance of high proportion of spinning-grade reserve, which violates the original intention in developing renewable energy generation. The use of flexible non-spinning-grade reserve will provide standby service and have great help to improve the adequacy of the system, which is an important way to promote the consumption of renewable energy. Aiming at the inadequacy of current optimization research in non-spinning-grade reserve, firstly, the dispatch mode and optimization model for non-spinning reserve on both the generation side and demand side are analyzed under the market mechanism. Then, a hybrid optimization method considering the differences and complementarities of spinning-grade and non-spinning reserve is proposed under multiple adequacy scenarios. Finally, detailed case studies verify the feasibility and effectiveness of the proposed optimization method.